Penghapusan Praktik Khitan Bagi Perempuan Dalam Peraturan Pemerintah Nomor 28 Tahun 2024: :(Perspektif Pengurus Cabang Lembaga Bahtsul Masail Nahdlatul Ulama Kota Malang dan Dokter Sp.OG pada Fakultas Kedokteran dan Ilmu Kesehatan Universitas Islam Negeri Maulana Malik Ibrahim Malang) - Priyatama, Januar Wahyu (Maliki Interdisciplinary Journal, 2025)
Circumcision is a practice that includes fitrah in Islam with the aim of maintaining cleanliness and health. Circumcision is not only carried out by men but also women. The discussion about female circumcision has resurfaced after the issuance of Article 102 letter (a) of Government Regulation Number 28 of 2024 concerning Regulation and the Implementation of Law Number 17 of 2023 concerning Health. The issuance of the regulation sparked debate from various circles, especially from Muslims and also the medical community. The researcher used an empirical juridical research type in which the researcher took three informants who were competent in their respective fields to respond to the elimination of the practice of circumcision in the regulation. The meaning of the abolition in Article 102 letter (a) can mean that the government no longer regulates the practice of female circumcision. It can be seen that until now there is no regulation that clearly regulates and explains the prohibition of female circumcision. The Chairman of the Malang City LBMNU emphasized that the regulation was considered excessive. Then the Sp.OG doctor at FKIK UIN Maulana Malik Ibrahim Malang stated that he did not completely reject the regulation, all returned to the operational definition related to the type of female circumcision removed by the regulation.